Reflection on Peer Assisted Learning at PAHS - KC, Anil; Karki, Sandesh (Journal of Patan Academy of Health Sciences, 2015)
Peer tutoring is an organized learning experience in which one student serves as the teacher or tutor, and one is the learner or tutee. Peerteachers and their students share a similar knowledge base and learning experience, which allows the peer-teachers to use language that their learners understand and to explain concepts at an appropriate level. Peerteachers and student-learners also share a similar social context because of their similar social roles, and because of this, student learners feel more at ease with a peer teacher than with a senior clinician. Peer tutoring is a beneficial way for students to learn from each other in the classroom and in small groups, so benefit is not only for the tutee but also to the tutor, predominantly through the development of their own clinical and teaching skills and from the positive feedback obtained by their tutees, thus creating a highly pleasant learning atmosphere and a win-win situation for all. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13020 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):54-56